Clinical and aetiological study of hand, foot and mouth disease in southern Vietnam, 2013–2015: Inpatients and outpatients. (March 2019) - Hoang, Minh Tu Van; Nguyen, To Anh; Tran, Tan Thanh; Vu, Thi Ty Hang; Le, Nguyen Truc Nhu; Nguyen, Thi Han Ny; Le, Thanh Hoang Nhat; Nguyen, Thi Thu Hong; Nguyen, Thanh Hung; Le, Nguyen Thanh Nhan; Truong, Huu Khanh; Du, Tuan Quy; et al.
Highlights: Multiple serotypes of enterovirus A cause hand, foot and mouth disease in southern Vietnam. Clinical characteristics differed slightly between the different pathogen groups. CV-A6 and CV-A10 emerged in Vietnam in 2013–2015. An unexpected dominance of EV-A71 was found among both inpatients and outpatients. Abstract: Background: Hand, foot and mouth disease (HFMD) has been associated with large outbreaks among young children in the Asia-Pacific Region since 1997, including cases of severe illness and death. Severe illness is often associated with enterovirus A71 (EV-A71). Vietnam experienced a large sustained outbreak of 200 000 hospitalized cases and over 200 deaths in 2011–12, the large majority occurring in southern Vietnam. Methods: A prospective observational study was conducted in the outpatient clinics, infectious diseases wards, and paediatric intensive care units of the three main referral centres for the treatment of HFMD in southern Vietnam. Demographic data, basic laboratory parameters, and clinical data were recorded, and molecular diagnostic tests were performed. Results: Between July 2013 and July 2015, a total of 1547 children were enrolled. Four serotypes of enterovirus A (EV-A71, Coxsackievirus (CV) A6, A10, and A16) were responsible for 1005 of 1327 diagnosed cases (75.7%). An unexpected dominance of EV-A71 was found among both inpatients and outpatients, as well as a strong association with severe illness. CV-A6 and CV-A10 emerged in Vietnam during the study period and replaced CV-A16. CV-A10 was associated with different clinical and laboratory characteristics. During admission, 119 children developed a more severe illness. It was found that children with a skin rash showed less progression of severity, but when a rash was present, a macular rash was significantly associated with an increased risk of progression. Conclusions: This study represents the most comprehensive descriptive HFMD study from Vietnam to date. Co-circulation and replacement of different serotypes has implications for vaccine development and implementation. These findings from a severely affected country add to our understanding of the presentation, progression, and aetiology of HFMD.